New Industrial Strategy for Europe: Main Challenges, Priorities - Шейко, І. А.; Помогалова, Н. В.; Возиловський, Д. М. (ХНУРЕ, 2022)
Industry plays an important role in the economic structure of the European Union. It accounts for 83 % of EU exports, and more than 30 million jobs. This makes it essential for the EU.
Keywords: industry; manufacturing; iIndustrial strategy; industrial economy